1985
DOI: 10.1126/science.3883489
|View full text |Cite
|
Sign up to set email alerts
|

Trypanothione: A Novel Bis(glutathionyl)spermidine Cofactor for Glutathione Reductase in Trypanosomatids

Abstract: Glutathione reductase from trypanosomes and leishmanias, unlike glutathione reductase from other organisms, requires an unusual low molecular weight cofactor for activity. The cofactor was purified from the insect trypanosomatid Crithidia fasciculata and identified as a novel glutathione-spermidine conjugate, N1,N8-bis(L-gamma-glutamyl-L-hemicystinyl-glycyl)spermidine, for which the trivial name trypanothione is proposed. This discovery may open a new chemotherapeutic approach to trypanosomiasis and leishmania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
375
0
11

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 660 publications
(401 citation statements)
references
References 22 publications
2
375
0
11
Order By: Relevance
“…Benzoyl chloride was purchased from Merck Schuchardt (Germany) and [1,[4][5][6][7][8][9][10][11][12][13][14] C]putrescine dihydrochloride (110 mCi/mmol) was obtained from NEN Life Science Products, Inc. (Boston, MA, USA). DFMO was a gift from the Merrell Dow Research Institute (Cincinnati, OH, USA).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzoyl chloride was purchased from Merck Schuchardt (Germany) and [1,[4][5][6][7][8][9][10][11][12][13][14] C]putrescine dihydrochloride (110 mCi/mmol) was obtained from NEN Life Science Products, Inc. (Boston, MA, USA). DFMO was a gift from the Merrell Dow Research Institute (Cincinnati, OH, USA).…”
Section: Chemicalsmentioning
confidence: 99%
“…Cells were collected by centrifugation (3000Ug, 10 min) and resuspended in fresh SDM-79 medium at a concentration of 2U10 8 parasites/ml with or without the addition of CHA. [1,[4][5][6][7][8][9][10][11][12][13][14] C]Putrescine (0.3 WCi/ml) was added and after incubation for 24^60 h at 28³C, parasites were sedimented, washed with PBS and resuspended in 100 Wl of 0.2 M perchloric acid. Cell extracts were neutralized with KOH and precipitates discarded after centrifugation.…”
Section: In Vivo Labeling With Radioactive Putrescinementioning
confidence: 99%
“…We evaluated more than 3,000 extracts from plant and fungi using an inhibition assay with trypanothione reductase (TR) (unpublished results). This enzyme is a validated molecular target in Trypanosoma and Leishmania species (Fairlamb et al 1985, Dumas et al 1997, Tovar et al 1998, Krieger et al 2000. As a result of the screening, we found that the ethyl acetate extract of the culture of Lentinus strigosus, a basidiomycete fungus belonging to the Polyporaceae family (Pegler 1983), was able to inhibit 100% of the enzyme activity at 20 µg/ml.…”
mentioning
confidence: 97%
“…:, o conhecimento desses alvos, graças ao desenvolvimento da genõmica, proteõmica e bioinformática (FAIRLAMB, 1999), permite antever futuro mais promissor na pesquisa de novos antichagásicos. Entre eles, sobressaem as proteases (McKERROW et ai., 1995) e a tripanotiona redutase (FAIRLAMB, CERAMI, 1985; FAIRLAMB et ai., 1985; JOCKERS-SCHERUBL, SCHIRMER, KRAUTH-SIEGEL,1989). Além da tripanotiona redutase e das enzimas auxiliares que sintetizam tripanotiona, a triparedoxina e a triparedoxina peroxidase, recentemente identificadas em T. cruzi por LOPEZ et ai.…”
Section: Alvos Bioquímicos Na Pesquisa De Novos Antichagásicosunclassified
“…É bem conhecida e relatada a deficiência do sistema de destoxificação do T.cruzi frente ao estresse oxidativo (VIODÉ et aI., 1997). Esse parasita não tem catalase e glutationa peroxidase e a glutationa redutase é substituída por enzima específica do parasito denominada tripanotiona redutase (FAIRLAMB, CERAMI, 1985; FAIRLAMB et aI., 1985; JOCKERS-SCHERUBL, SCHIRMER, KRAUTH-SIEGEL,1989; HENDERSON et aI., 1991). A tripanotiona redutase constitui-se em um dos principais alvos do planejamento de novos antichagásicos (FAIRLAMB, 1999).…”
unclassified